PERAN ASESMEN KEBUTUHAN DALAM OPTIMALISASI PERENCANAAN PENDIDIKAN DI ERA MERDEKA BELAJAR - Reannisa, Farraz; Lorenta, Hasianna; Aghnia, Syifa Nur; Rismiyati, Luthfia Amni; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the strategic role of needs assessment in the educational planning process, particularly within the context of the Merdeka Belajar (Freedom to Learn) policy. In an education system that is continuously undergoing transformation, needs assessment serves as a crucial foundation for designing planning that is relevant, adaptive, and based on the actual conditions of students and educational institutions. The research uses a descriptive qualitative approach through a literature review of various relevant scientific sources. The findings show that needs assessment is capable of identifying gaps between the ideal and actual conditions in various aspects of education, such as student competencies, teacher readiness, and the availability of learning infrastructure. The Merdeka Belajar policy provides schools and teachers with greater autonomy in designing contextual curricula and learning processes. However, without proper needs assessment, educational planning risks being misaligned with on-the-ground realities. The study also reveals that the implementation of needs assessment in schools still faces several challenges, including limited teacher competence, time constraints, and weak institutional support. Therefore, strengthening strategies are needed, such as teacher training, the development of practical assessment instruments, and the integration of assessment results into school planning documents. Thus, needs assessment not only functions as a tool for identifying problems but also as a foundation for effective decision-making in educational planning that prioritizes quality and equitable learning. This research is expected to contribute to the development of educational policy and practice that is more responsive to actual needs in the era of Merdeka Belajar.